Geriatrisches Assessment – Was sollte vor Therapiebeginn des mHSPC und des mCRPC gemacht und bedacht werden? - Heers, Hendrik; Butea-Bocu, Marius Cristian; Groeben, Christer; Huber, Johannes; Wullich, Bernd; Goebell, Peter; Fiebig, Christian (Aktuelle Urologie, 2023)
The systemic treatment of prostate cancer nowadays is predominantly carried out with combination therapies. A range of aspects should be respected in older and comorbid patients, in order to avoid toxicities and to achieve a successful therapy alongside good quality of life. The definition of geriatric patients is not primarily based on chronological age but rather on the overall health condition and life expectancy. Comorbid patients > 70 years should undergo a three-step geriatric screening before treatment initiation. If the G8 screening and/or mini-COG shows abnormalities (taking into account nutrition, comorbidity/medication, mobility, and cognition), a simplified geriatric assessment is recommended. Patients can then be stratified into three groups (fit, vulnerable, frail). Only a few cases warrant a complete geriatric assessment. Treatable deficits in the above mentioned domains should be improved if possible. When choosing a systemic therapy, fit patients can be treated the same as non-geriatric patients. Vulnerable and frail patients are under a higher risk for toxicities, so special care should be taken. While the diverse substances of hormonal therapy are usually well tolerated (even though some substance-specific toxicities can occur), haematotoxic substances such as taxanes or olaparib can only be recommended in select cases. As falls - especially under hormonal therapy - are a common problem, osteoprotective therapy should especially be considered. Upon progression of the tumour disease, there should not be a reflex to simply switch to the next line of treatment, but an individual concept should be established together with the patient and his relatives, taking into account aspects of palliative care and patient needs and focussing on quality of life and also setting therapy limitations.
CRIS-Team Scopus Importer:2023-10-13
Keywords: chemotherapy; geriatrics; hormonal therapy; personalised medicine; prostate cancer